2015
DOI: 10.1021/am507573m
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Solvent Driven Actuation of Polyelectrolyte Multilayers Based on Modulation of Dynamic Secondary Interactions

Abstract: Polyelectrolyte multilayers (PEMs), assembled from weak polyelectrolytes, have often been proposed for use as smart or responsive materials. However, such response to chemical stimuli has been limited to aqueous environments with variations in ionic strength or pH. In this work, a large in magnitude and reversible transition in both the swelling/shrinking and the viscoelastic behavior of branched polyethylenimine/poly(acrylic acid) multilayers was realized in response to exposure with various polar organic sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 54 publications
5
42
0
Order By: Relevance
“…While these composites require an external electric field and just available for strain change, flowable polyelectrolytes in layer‐by‐layer assembled polyelectrolyte multilayers (PEMs) can achieve intrinsic self‐healing of surface defects by simply being wet with water, a large simplification over other approaches such as the inclusion of embedded healing agents . Weak polyelectrolyte complexes become viscous upon contact with water, and even show strong adhesive property if sufficiently concentrated . Such facile self‐healing behavior can be used to extend the lifetime of actuating materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While these composites require an external electric field and just available for strain change, flowable polyelectrolytes in layer‐by‐layer assembled polyelectrolyte multilayers (PEMs) can achieve intrinsic self‐healing of surface defects by simply being wet with water, a large simplification over other approaches such as the inclusion of embedded healing agents . Weak polyelectrolyte complexes become viscous upon contact with water, and even show strong adhesive property if sufficiently concentrated . Such facile self‐healing behavior can be used to extend the lifetime of actuating materials.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most attractive features of electrostatically bound PEMs prepared by the LbL process is the controllable charge density of the PE chains, which can be adjusted by either controlling ionic strength of the surrounding aqueous solution for strong PEs or changing the ionic strength as well as solution pH for weak PEs with labile functional groups (e.g., carboxylic acid) . This ability to modulate polyelectrolyte charge density will in turn tune the properties of the PEMs, creating changes in thickness, swelling/shrinking states, elastic properties, porosity, wettability, and even generates determined mechanical motions . This makes PEMs, especially those made from weak polyelectrolytes, ideal for responsive materials, such as pH, electric field, and electrochemically induced swelling in water, thermoresponsive film expansion, and humidity controlled curling behavior as well as “walking.” However, for these diverse reversible actuators, thin PEMs are preferable to achieve significant dynamic motion, which limits the adhesive force as well as PE migration rate needed for effective self‐healing performance when the PEs are ionically bound to the underlying substrate …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The film shrinks to its original thickness (≈700 nm for 8‐BL) after drying at 70 °C for 30 min. It has been reported that this reversible swelling‐drying cycle can be repeated at least ten times without damaging the multilayer nanocoating . This 8‐BL PEI/PAA nanocoating reduces the OTR of 179 µm PET to the undetectable limit of commercial instrumentation (<0.005 cc (m −2 d −1 )) .…”
Section: Resultsmentioning
confidence: 95%
“…It has been reported that this reversible swelling-drying cycle can be repeated at least ten times without damaging the multilayer nanocoating. [52] This 8-BL PEI/PAA nanocoating reduces the OTR of 179 µm PET to the undetectable limit of commercial instrumentation (<0.005 cc (m −2 d −1 )). [45] This low OTR originates from the strong ionic interaction between the polyelectrolyte chains, which results in small free volume in the nanocoating.…”
Section: Resultsmentioning
confidence: 99%